INTERPROFESSIONAL SHARED DECISION-MAKING: A LITERATURE REVIEW - Chaina Hanum; Ardi Findyartini (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2020)
Background: The increasing complexity of health problems consequently demands problem solving from various perspectives of health professionals. The interprofessional approach in solving health problems, by working together with patients, their families, and the communities is called Interprofessional Shared Decision-Making (IP-SDM). The capability of various health professionals in IP-SDM becomes one of the abilities to be achieved in Interprofessional Collaborative Practice (IPCP). IP-SDM learning should also be achieved through Interprofessional Education (IPE).Method: This is a literature study aiming to elaborate IP-SDM and its correlation to IPCP and IPE.Results: IP-SDM is a decision making process which involves collaboration between two or more health professionals and also patients aiming at idenfication of best choices while considering patients’ preferences. IP-SDM consists of two core processes: shared decision-making (SDM) between health professionals and patients and collaborative clinical reasoning (CCR) among health professionals. Conclusion: Although SDM and CCR learning has been widely reported, including the potential emphasis in interprofessional education and interprofessional collaborative practice, IP-SDM learning is still limited. For this particular reason, further exploration is needed regarding the development of IP-SDM learning method in IPE, especially in Indonesia context.